Influence of vanadium-doping on the magnetism of FeCo/SiO2 nanoparticle. Issue 25 (27th May 2016) - Desautels, Ryan D.; Rowe, Michael P.; Freeland, John W.; Jones, Michael; van Lierop, Johan
Abstract : How the formation of vanadium silicate, at the interface between a SiO2 -coating and the FeCo nanoparticle it encapsulates, modifies the magnetic coercivity and induces an exchange bias. Abstract : FeCo nanoparticles (4 ± 1 nm), encapsulated by SiO2, were synthesized with and without a 2% (atomic ratio) vanadium doping. The impact from the presence of vanadium, an additive often used in the bulk to alter both physical and mechanical properties, on the nanomagnetism was probed by element-specific X-ray spectroscopy and magnetometry techniques. While the nanostructure was unaffected by the addition of 2% vanadium, the temperature dependent magnetic properties were altered significantly, such as the increased coercivity and an exchange bias field shift.